Only paradoxes to offer : French feminists and the rights of man - Scott, Joan Wallach (Harvard University Press, 1996)
When feminists argued for political rights in the context of liberal democracy they faced an impossible choice. On the one hand, they insisted that the differences between men and women were irrelevant for citizenship. On the other hand, by the fact that they acted on behalf of women, they introduced the very idea of difference they sought to eliminate. This paradox - the need both to accept and to refuse sexual difference in politics - was the constitutive condition of the long struggle by women to gain the right of citizenship. In this new book, remarkable in both its findings and its methodology, award-winning historian Joan Wallach Scott reads feminist history in terms of this paradox of sexual difference.